Development of the 'QAF' Teaching Materials based on the Relevance of Stories for Third Grade Elementary School Students - Teranggano, Haula; Nurrohim, Ahmad; Aisyah, Septi; Syahroni, Asma; Muttakhida, Istna Aliya (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
The observations and interviews conducted at SDN Harapan found that the teaching materials for memorizing the Qur'an in elementary schools, in general, have not produced a strong long-term memorization quality in students who memorize the Qur'an. This research aims to develop teaching materials for memorizing the Qur'an based on reasonable, practical, and effective stories. This type of research is research and development. The development model used is the Plomp model, which consists of 5 stages, namely analysis, design, development, implementation, and evaluation. Practicality test data was obtained from the results of observation analysis of learning implementation, which was used in this study, which was quantitative descriptive data analysis and qualitative descriptive data analysis. The research data collection instruments are a validation questionnaire for media and material experts, a questionnaire on the practicality of teacher and student responses, and a test in the form of a post-test. The post-test results obtained a score percentage of 80% and met the effective criteria. It can be concluded that the "QAF" teaching material based on the story developed meets the practical and effective criteria.